Pengaruh Personal Branding, Soft Skill, dan Locus Of Control terhadap Kesiapan Kerja Mahasiswa Politeknik Aceh - Vadia Aqilah; Febyolla Presilawati; Yuslaidar Yusuf (Politeknik Kampar, 2024)
This study aims to determine whether personal branding, soft skills, and locus of control have an influence on the work readiness of Aceh polytechnic students and to find out the combination of personal branding, soft skills, and locus of control has an influence on work readiness. The population used in this study were all active students of Aceh Polytechnic totaling 73 people. This study uses a data collection method using a questionnaire with survey research as a data collection technique. Hypothesis testing in this study used multiple linear analysis methods, F test, T test and coefficient of determination (R2). The results showed that in partial tests between personal branding variables had no effect on work readiness, while soft skills variables, and locus of control had a partial test effect on work readiness. Then simultaneously test the variables of personal branding, soft skills, and locus of control affect work readiness. The implications of this study indicate that soft skills, and locus of control have a greater role in increasing the work